PENGEMBANGAN ASESMEN PEMBELAJARAN MENGGUNAKAN APLIKASI WORDWALL DI SD NEGERI 99 PALEMBANG - Putri Vannisa, Saprina; Nurlaila, Nurlaila; Fatimah, Siti (STKIP Subang, 2026)
Assessment development using the Wordwall application is the process of creating an interactive assessment tool using the Wordwall application. The purpose of this study was to determine the feasibility level as well as the practicality of the assessment products developed. This research is a development research (Research and Development) with a 3D research model (Define, Design and Develop) modification of the 4D research model developed by Thiagarajan. The validation results from material experts are 95% which are included in the very valid category. The results of validation from media and language experts are 92.5% which is included in the very valid category. The results of small group trials by 8 students were 92.5% which is still in the very practical category. The results of the large group trial by 27 students were 96% which was in the very practical category. From these results, the assessment product using the Wordwall application is declared valid and also practical for use in learning activities. Furthermore, it is hoped that th is assessment product can be applied to other subjects so that it helps teachers and students to teach and learn better.